Two amino acids in each of D(1) and D(2) dopamine receptor cytoplasmic regions are involved in D(1)-D(2) heteromer formation - O’Dowd, Brian F. (Biochem Biophys Res Commun, 2011)
D(1) and D(2) dopamine receptors exist as heteromers in cells and brain tissue and are dynamically regulated and separated by agonist concentrations at the cell surface. We determined that these receptor pairs interact primarily through discrete amino acids in the cytoplasmic regions of each receptor, with no evidence of any D(1)-D(2) receptor transmembrane interaction found. Specifically involved in heteromer formation we identified, in intracellular loop 3 of the D(2) receptor, two adjacent arginine residues. Substitution of one of the arginine pair prevented heteromer formation. Also involved in heteromer formation we identified, in the carboxyl tail of the D(1) receptor, two adjacent glutamic acid residues. Substitution of one of the glutamic acid pair prevented heteromer formation. These amino acid pairs in D(1) and D(2) receptors are oppositely charged, and presumably interact directly by electrostatic interactions.